Digital radiography for the inspection of weld seams of pipelines - better sensitivity - Moreira, Edson Vasques; Simõesa, Heleno Ribeiro; Rabello, José Maurício Barbosa; de Camargo, José Rubens; Pereira, Marcelo dos Santos [UNESP] (Taylor & Francis, 2010)
Conventional radiography, using industrial radiographic films, has its days numbered. Digital radiography, recently, has taken its place in various segments of products and services, such as medicine, aerospace, security, automotive, etc. As well as the technological trend, the digital technique has brought proven benefits in terms of productivity, sensitivity, the environment, tools for image treatment, cost reductions, etc. If the weld to be inspected is on a serried product, such as, for example, a pipe, the best option for the use of digital radiography is the plane detector, since its use can reduce the length of the inspection cycle due to its high degree of automation. This work tested welded joints produced with the submerged arc process, which were specially prepared in such a way that it shows small artificial cracks, which served as the basis forcomparing the sensitivity levels of the techniques involved. After carrying out the various experiments, the digital meth odshowed the highest sensitivity for the image quality indicator (IQI) of the wire and also in terms of detecting small discontinuities, indicating that the use of digital radiography using the plane detector had advantages over the conventional technique (Moreira et al. Digital radiography, the use of plane detectors for the inspection of welds in oil pipes and gas pipes.9th COTEQ and XXV National Testing Congress for Non Destructive Testing and Inspection; Salvador, Bahia, Brazil and Bavendiek et al. New digital radiography procedure exceeds film sensitivity considerably in aerospace applications. ECNDT; 2006; Berlin). The works were carried out on the basis of the specifications for oil and gas pipelines, API 5L 2004 edition (American Petroleum Institute. API 5L: specification for line pipe. 4th ed. p. 155; 2004) and ISO 3183 2007 edition (International Organization for Standardization, ISO 3183. Petroleum and gas industries - steel pipes for pi pelines transportation systems. p. 143; 2007). © 2010 Taylor & Francis.
Keywords: Digital radiography; Gas-lines; Industrial radiographic films; Oil-lines; Welding; American Petroleum Institute; Artificial cracks; Conventional techniques; Degree of automation; Digital techniques; Film sensitivity; Gas pipes; Image treatment; Inspection cycles; International organization for standardizations; Line pipes; Non destructive testing; Oil pipes; Oil-and-Gas pipelines; Plane detector; Products and services; Radiographic films; Submerged arc; Technological trends; Transportation system; Weld seam; Welded joints; Aerospace applications; Cost reduction; Detectors; Gas pipelines; Gases; Image quality; Inspection; International cooperation; Nondestructive examination; Petroleum transportation; Pipe; Pipelines; Radiology; Specifications; Tropical engineering; Welded steel structures; Welds; X ray films; Industrial radiography